A novel phased‐concept course for the delivery of anatomy and orthopedics training in medical education. Issue 4 (21st December 2016) - Klima, Stefan; Hepp, Pierre; Löffler, Sabine; Cornwall, Jon; Hammer, Niels
Abstract : Integration of anatomy and clinical teaching is a theoretical ideal, yet there is a worldwide paucity of such amalgamation. These teaching models provide support for medical trainees, an important element in Germany where orthopedic intern numbers have declined and anecdotal evidence suggests disinterest in orthopedics. The aim of the study was to develop an integrated anatomy‐surgical course for undergraduate medical training, assess the model developed, and explore how medical students perceive orthopedics as a career. The course was to deliver medical anatomy and clinical orthopedic training, focusing on interdisciplinary teaching and learning, vertical integration of clinical knowledge and skills, and professional interaction. Survey evaluation of the course and students' perceptions of orthopedic careers was performed, including Likert‐type responses rating variables of interest. A phased‐concept program of five courses, each optional and under one‐week in duration, was developed parallel to the undergraduate medical program. Delivered by anatomists and surgeons, courses included biomechanics, advanced dissection, surgical approaches, casts and implants, and sports medicine. Course data indicate positive support for course format, stimulation of interest, and high clinical relevance. Students are generally interested in surgery, and identify hierarchy, lawsuits, bureaucracy and physical stress as barriers to orthopedic careers. This novel phased‐concept successfully delivers combined anatomy and surgery training in a vertically‐integrated format while addressing students' clinical and professional skills. The format facilitates an appreciation of potential career options in orthopedics, while fostering professional skills during medical training. Barriers to careers in orthopedics can now be addressed in future courses. Anat Sci Educ 10: 372–382. © 2016 American Association of Anatomists.